THE THEORY OF THE INTERNALLY STUDENTIZED RANGE DISTRIBUTION REVISITED - FERREIRA, Daniel Furtado; CHAVES, Lucas Monteiro; SOUZA, Devanil Jaques de (Brazilian Journal of Biometrics, 2018)
The present paper intends to revisit the distribution of the ratio of the range to the sample standard deviation, known as the distribution of the internally studentized range, in the normal case. This distribution has its importance recognized in several areas, as quality control and inference, for testing the lack of homogeneity of the data or kurtosis. An alternative distribution to the one presented by David et al. (1954), based on the distribution of the maximum, is proposed. We exhibit a detailed proof for the distribution of the internally studentized range in the normal case and sample size 3. We also provide a new result: the distribution for the uniform case with sample of size 3.